COMPARATIVE EFFECTIVENESS OF TAMSULOSIN VERSUS STANDARD MEDICAL THERAPY FOR MEDICAL MANAGEMENT OF SMALL URETERIC STONES - Khan, Aya; Ahmad, Tanveer; Khan, Ismail; Khattak, Ikram Ullah (Journal of Postgraduate Medical Institute, 2018)
Objective: To investigate and compare the effectiveness of tamsulosin versus standard medical therapy (SMT) for conservative management of ureteric stones in terms of time needed for stone expulsion, reduction in pain episodes and stone expulsion rates. Methodology: This was a prospective non-blinded, non-randomised controlled study conducted at Urology Unit, LRH Peshawar, from July 2015 to June 2016. 50 patients were included, 25 patients in Group 1 (SMT) and 25 patients in Group 2. All patients were selected consecutively from the outpatient department with a stone size â‰¤10 mm. In Group 1, patients were prescribed adequate oral analgesics while Group 2 patients were given tamsulosin plus analgesics for pain relief on as need basis. Data was obtained about symptoms duration, stone size, stone location, total pain episodes and the time to passage of stone. Results: There were 35 (70%) males and 15 (30%) females with a ratio of 2.3:1. Overall mean age was 31.84 ±5.64 years; range was 22 to 42 years; and mean duration of symptoms was 6.64 ±1.48 days. The overall mean stone size was 5.94 ±1.46 mm (range 4 mm to 9 mm). Significant differences were detected in total pain episodes (mean pain episodes for group 1= 3.64 & group 2= 1.6, p <0.0001) and stone passage time (mean passage time for group 1= 17.52 ±7.22 days & group2 = 10.44 ± 5.64 days, p <0.0001). Conclusions: Tamsulosin effectively reduce the time needed for spontaneous expulsion of ureteric stones. It increases the rate of stone passage and importantly reduces the number of pain episodes.